Inflation, Government Expenditure, and Economic Growth in Indonesia - Ratu Ahdini Magfuroh Mandala (Jambura Equilibrium Journal, 2020)
This study estimates long run and short run association between inflation, government expenditure, and economic growth in Indonesia from 1981 to 2018. This study run diagnostic and specification test on time-series datasets in the model. This study employs Engel-Granger Cointegration Test and Error Correction Model (ECM) to estimate the long run and short run association in the model. This study further disaggregates government expenditure data in Indonesia into routine and development expenditure to analyse the individual and combined effect of the variable in the model. Result of the study suggested that the association between inflation and economic growth is negative, while the association between government expenditure and economic growth is positive. Moreover, routine expenditure has insignificant effect. Finally, ECM concluded that short-term adjustment in the model is less than one percent and specifically stable in all regression models. Keywords: Inflation, Government Expenditure, Economic Growth, ECM.